OP74 Marriage and physical functioning at older ages in England. (2nd September 2014) - Wood, N; Stafford, M; McMunn, A; Webb, E
Abstract : Background: Married people have lower rates of mortality and report better physical and mental health at older ages, compared to the unmarried. Few studies have investigated marriage and physical functioning at older ages and only one has investigated the association using objectively assessed physical functioning. Given declining marriage rates and increasing prevalence of divorce in the last 40 years, more people are now entering older ages unmarried, or with varied marital histories. Marital history comprises previous marital statuses, transitions in and out of marriage and duration spent in each marital status. The aim of this paper is to investigate marriage and its association with physical functioning among those aged 50+ using nationally representative data from England. Methods: The English Longitudinal Study of Ageing (ELSA) comprises approximately 10, 000 people aged 50+ in England. Physical functioning was captured in 2008 objectively by measuring grip strength (in kgs) using a dynamometer and walking speed (in metres per second) by timing respondents walking a distance of 2.44 metres. Multiple linear regression was used to investigate the association. The measure of marital status included elements of marital history through differentiating between first marriage, remarriage, divorced, widowed and never married. Results: Never married men had a slower walking speed, -0.066 m/s (95% CI -0.13015 to -0.00229) compared to the continually married, adjusted for age, education and wealth. Although walking speed was lower for smokers, those less physically active, those with higher body mass index, those with poor self-rated health and those with more chronic health conditions, adjustment for these did not explain the association between men's walking speed and marital status. Never married women had a slower walking speed than those continually married, -0.063 m/s (95% CI -0.12005 to -0.00616) when controlling for age, education and wealth, but this was explained by health behaviours and health conditions. Never married men also had weaker grip strength than the continually married, -1.085 kgs (CI -1.93425 to -0.23627) when adjusted for age, education and wealth, but this difference was largely explained by health behaviours. There were no such differences among women and never married women had comparable grip strength to those who were continually married. Conclusion: The results confirm a previous study indicating that marriage may be protective for men's physical functioning. Alternatively better health in earlier life may select men into marriage, resulting in better physical functioning in older ages. Marriage does not have the same benefits for women's physical functioning.